Plant-Induced Soil Changes: Processes and Feedbacks 1998
DOI: 10.1007/978-94-017-2691-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Soil interactions in temperate grasslands

Abstract: We present a conceptual model in which plant-soil interactions in grasslands are characterized by the extent to which water is limiting. Plant-soil interactions in dry grasslands, those dominated by water limitation ('belowground-dominance'), are fundamentally different from plant-soil interactions in subhumid grasslands, where resource limitations vary in time and space among water, nitrogen, and light ('indeterminate dominance'). In the belowgrounddominance grasslands, the strong limitation of soil water lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(181 citation statements)
references
References 76 publications
4
173
3
1
Order By: Relevance
“…Once established in the marsh, woody plants are believed to generate below-canopy resource islands through autogenic nutrient and peat redistribution mechanisms (Burke et al 1998;Wetzel et al 2005). Rietkerk et al (2004) described one such mechanism occurring in temperate peatlands, where mass flow of groundwater nutrients, especially nitrogen (N), move towards areas with higher vascular plant biomass due to differential transpiration rates.…”
Section: Introductionmentioning
confidence: 99%
“…Once established in the marsh, woody plants are believed to generate below-canopy resource islands through autogenic nutrient and peat redistribution mechanisms (Burke et al 1998;Wetzel et al 2005). Rietkerk et al (2004) described one such mechanism occurring in temperate peatlands, where mass flow of groundwater nutrients, especially nitrogen (N), move towards areas with higher vascular plant biomass due to differential transpiration rates.…”
Section: Introductionmentioning
confidence: 99%
“…Lower C:N ratios make plant inputs of higher quality (Burke et al 1998) so roots are more easily decomposed by microbes, providing needed carbon to denitrifiers.…”
Section: Categorymentioning
confidence: 99%
“…The aboveground net primary productivity (ANPP) of the grasslands of North America is strongly influenced by the amount and distribution of annual precipitation (Sala et al 1988). Where available moisture is less limiting, changes in nutrient supply can have major influences on grassland primary productivity, plant species composition, litter quality, N availability and SOC sequestration (Wedin and Tilman 1996;Burke et al 1998;Schuman et al 1999;Franzlubbers et al 2000;Schnabel et al 2001;Weinhold et al 2001). In intensively managed pastures of the humid regions of North America, Franzlubbers et al (2000) concluded that appropriate grazing strategies can produce C gains up to 1000 kg C ha -1 yr -1 .…”
Section: Mots Clésmentioning
confidence: 99%
“…Tame pastures of crested wheatgrass (CWG) (Agrpyron cristatum) with and without alfalfa (Medicago sativa) were compared at various levels of fertility inputs, stocking density and season length. As the overriding constraint of water limitation diminishes with increasing annual precipitation, herbivory and soil nitrogen, in addition to fire and light, gain in importance in determining grassland plant community and ecosystem dynamics (Burke et al 1998). The drier prairie regions (Moist Mixed and Mixed Grassland) were considered too dry to experience benefits from N fertilization (FERT), seeded pastures of grass/legume grazed continuously (GLGC) or rotationally (GLGR), or complementary grazing (CG) practices.…”
Section: Modeling Forage Yields Livestock Productivity and Profitabimentioning
confidence: 99%
See 1 more Smart Citation